A Note on Primitive Permutation Groups of Prime Power Degree. (11th January 2015) - Cai, Qian; Zhang, Hua
Abstract : Primitive permutation groups of prime power degree are known to be affine type, almost simple type, and product action type. At the present stage finding an explicit classification of primitive groups of affine type seems untractable, while the product action type can usually be reduced to almost simple type. In this paper, we present a short survey of the development of primitive groups of prime power degree, together with a brief description on such groups.